Mega-churches and the neo-Pentecostalisation of South Africa's black middle class - Ngoma, Amuzweni Lerato (Rhodes University, Faculty of Humanities, Department of Sociology)
This thesis argues that the presence and expansion of South African neo-Pentecostal Charismatic Churches (neo-PCCs) and mega-churches holds significant political economy consequences. Methodologically, the thesis is anchored on digital and in-person ethnography, life history and in-depth interviews. The central argument of this thesis is that neo-PCCs and mega-churches are holding spaces for societal change. The symbolic capital of neo-PCCs and mega-churches and the neo-Pentecostalised habitus, which is co-produced by middle-classes acts as a conduit that facilitates social transitions of political and economic orders. Indeed, religion emerges as a transition mechanism as Durkheim argued for France. It has helped South African social groups to extricate themselves from racist discourses, foster non-racialism and build empowered, somewhat deracialised modern middle-class discourses and tastes. White and Black middle classes have co-produced neo-Pentecostal habiti in the post-apartheid era, that have first, built dispositions for neoliberal capital democracy from apartheid capitalism, second as a middle classing and elite making mechanism and field, third as a stabilising, consolidating and upward strategy of social reproduction. In this way, neo-PCCs and the Black middle class have significantly affected the post-apartheid social formation by producing dispositions that uphold financialised neoliberal capitalism. Significantly, accumulated cultural capital is an indispensable resource in initiating and building post-apartheid institutions. As in the neo-PCC field, it has been pastors, prophets and bishops that have demonstrated the capability to accumulate, transubstantiate and maintain cultural capital that has made their churches comparatively durable social institutions. In a political economy context of state-capture and corruption, a post-GFC-and-COVID-19 milieu characterised by the absence of economic growth, rising unemployment, business closure and ever-increasing interest rates that affect indebted middle-class households and the poor alike, the mega-churches studied herein and their neo-Pentecostalised Black middle class adherents expressed an intense dislike for South African politicians across party lines, and especially the poor performance of the African National Congress-dominated state. So that it is possible that mega-churches and their leaders will outlive many new political parties and independents in the same way that they have outlived post-1994 political parties such as the New National Party, Agang South Africa and the Independent Democrats. Much like the buffer Black middle class that was promoted by the apartheid state as a project of reforming apartheid in the 1970s, whose political activism was pragramatically disengaged, this will likely continue, unless if, generally the post-apartheid Black middle classes shift their sociality from in-ward looking-enclaved social anxiety.
Keywords: Megachurch; Charismatic Movement; Pentecostalism -- South Africa; Middle class Black people -- South Africa; Bourdieu, Pierre, 1930-2002; Habitus (Sociology); Social capital (Sociology)